Metal anticorrosive coating based on phosphotungstic acid modified carbon nitride / epoxy resin and preparation method thereof

By adding phosphotungstic acid-modified carbon nitride filler to the epoxy resin coating, the problem that microcracks and internal micropores are easily formed during the curing process of the epoxy resin coating, which significantly improves the durability and anti-corrosion effect of the coating.

CN119859452APending Publication Date: 2025-04-22NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510109768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The pure epoxy resin coating is prone to microcracks and internal micropores during the curing process, resulting in their prone to failure, short service life and average anti-corrosion effect.

Method used

The graphite phase carbon nitride is modified by phosphotungstic acid as filler, and the graphite phase carbon nitride is modified by phosphotungstic acid to form a two-dimensional sheet structure, mixed in bisphenol A liquid epoxy resin, and then sonicated and vacuum-preserved to form a coating, which is coated on a metal substrate for curing.

Benefits of technology

By filling microcracks and internal micropores, the durability of the epoxy resin coating is significantly improved, and through the release of phosphotungstic acid and the formation of FeWO4 and Fe2(WO4)3, a dense mesh film is formed, effectively suppressing corrosion, extending the coating's usage time and anti-corrosion effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859452A_ABST
    Figure CN119859452A_ABST
Patent Text Reader

Abstract

The invention discloses a metal anti-corrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin and a preparation method of the metal anti-corrosion coating, and belongs to the technical field of metal coatings. According to the coating, phosphotungstic acid modified carbon nitride is added into an epoxy resin coating, and on one hand, the phosphotungstic acid modified carbon nitride can utilize a two-dimensional sheet structure of the phosphotungstic acid modified carbon nitride to fill microcracks and internal micropores; on the other hand, when the coating is damaged, phosphotungstic acid of the coating can release anions, the anions and iron ions on the metal surface generate indissolvable FeWO4 and Fe2 (WO4) 3, gaps and defects of the damaged position of the coating are filled up, the protection time of the anti-corrosion coating is long, a certain protection effect still exists after the coating is slightly damaged, and the anti-corrosion performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy resin coatings, and specifically relates to a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin and a preparation method thereof. Background Art

[0002] With the development of industry and the substantial progress of metallurgical technology, metal materials are widely used in all aspects of construction, transportation, aviation and power systems. However, the impact of metal materials' easy corrosion and failure has begun to limit the development of metal materials. Therefore, the research on anti-corrosion methods for metal materials has begun to be taken seriously. Traditional metal anti-corrosion methods include electroplating, electrochemical protection and adding sustained-release agents, but these methods all have certain defects. For example, the electroplating process is complex and costly and is not suitable for large-scale application. The electrochemical protection method requires a specific power source or active metal and is limited in scale. The general components of the sustained-release agent are destructive to the environment.

[0003] In order to improve the anti-corrosion performance of metals safely and multi-purposely, organic coatings are favored, especially epoxy resin coatings among organic coatings, which have a wide range of applications, low cost, high chemical stability and good insulation. However, pure epoxy resin coatings are prone to form microcracks and internal micropores during the curing process. Microcracks and internal defects will be invaded by elements necessary for corrosion such as oxygen molecules and chloride ions during use, causing the epoxy resin coating to fail quickly, resulting in a shorter-than-expected service life and a general anti-corrosion effect. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a metal anti-corrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin and a preparation method thereof, so as to solve the problem that pure epoxy resin coatings in the prior art are prone to form microcracks and internal micropores during the curing process, which leads to the problem that the epoxy resin is prone to failure.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin comprises the following steps: S1, modifying graphite phase carbon nitride by phosphotungstic acid to obtain two-dimensional sheet-like phosphotungstic acid-modified carbon nitride; S2, mixing bisphenol A liquid epoxy resin, a curing agent and phosphotungstic acid modified carbon nitride and stirring them uniformly, and obtaining a coating after ultrasonic treatment; S3, coating the paint on the metal substrate, and obtaining the epoxy resin metal anti-corrosion coating after drying and curing.

[0006] A further improvement of the present invention is: Preferably, in S2, the mixing mass ratio of bisphenol A liquid epoxy resin and curing agent is 1:(0.7-0.9).

[0007] Preferably, it is characterized in that the mass fraction of phosphotungstic acid modified carbon nitride in the coating is 0.25 wt%~0.75wt%.

[0008] Preferably, in S2, the bisphenol A liquid epoxy resin is preheated at 45° C.-75° C. for 5-15 minutes before being mixed with the curing agent and the phosphotungstic acid modified carbon nitride.

[0009] Preferably, in S2, the ultrasonic treatment time is 5-15 minutes.

[0010] Preferably, in S2, the coating is stored in a vacuum environment for 5-10 minutes after ultrasonic treatment.

[0011] Preferably, in S2, the curing agent is any one of anhydride 80-150, amine room temperature -80 or polyamide 25-60.

[0012] Preferably, the specific process of S3 is: coating the coating on the metal substrate, first storing it at 100° C. for 10 hours, and then storing it at 150° C. for another 4 hours.

[0013] Preferably, in S1, the process of treating graphite phase carbon nitride with phosphotungstic acid is as follows: calcining melamine to prepare g-C3N4, and sintering g-C3N4 and phosphotungstic acid to obtain phosphotungstic acid modified carbon nitride.

[0014] A metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin prepared by any one of the above preparation methods comprises epoxy resin, in which two-dimensional flaky phosphotungstic acid modified carbon nitride is embedded.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin. During the preparation process, two-dimensional flaky phosphotungstic acid modified carbon nitride is added to bisphenol A liquid epoxy resin, and the final epoxy resin coating formed after curing contains phosphotungstic acid modified carbon nitride as a filler. On the one hand, the phosphotungstic acid modified carbon nitride can use its own two-dimensional flaky structure to fill microcracks and internal micropores, thereby greatly improving the durability of the epoxy resin coating. On the other hand, the presence of phosphotungstic acid in the filler releases anions under the reduction effect of the polymer when the coating is damaged, and generates insoluble FeWO4 and Fe2(WO4)3 with the iron ions on the metal surface, filling the gaps and defects in the damaged coating, and forming a dense network film together with the oxide film of the metal itself, thereby inhibiting corrosion; and for carbon nitride itself, it is a wide bandgap semiconductor, and its bandgap width enables it to absorb ultraviolet light and part of visible light. When electrons are excited from the valence band to the conductive band under light, H2O reacts with electrons to produce H2 and reacts with holes to produce O2. Therefore, adding carbon nitride can effectively remove corrosive media such as H2O, thereby inhibiting the corrosion rate.

[0016] The present invention also discloses a metal anti-corrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin. The anti-corrosion coating can provide long protection time and still has a certain protective effect after the coating is slightly damaged. The anti-corrosion performance is excellent, and the service life and anti-corrosion effect of the epoxy resin coating can be greatly improved, thereby further improving the application scope of epoxy resin in the field of anti-corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the infrared test result of phosphotungstic acid modified carbon nitride; Figure 2 This is the salt spray test result diagram; Figure 3 Side view of water contact angle; (a) is pure epoxy sample; (b) is 0.25 wt% sample; (c) is 0.5 wt% sample; (d) is 0.75 wt% sample; Figure 4 Scanning electron microscope images of the samples; among them, (a) is a pure epoxy sample; (b) is a 0.25 wt% sample; (c) is a 0.5wt% sample; and (d) is a 0.75 wt% sample. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0020] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0021] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0022] The first aspect of the present invention discloses a method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin, which specifically comprises the following steps: S1, after modifying graphite phase carbon nitride with phosphotungstic acid, a two-dimensional sheet of phosphotungstic acid-modified graphite phase carbon nitride is obtained, which is ground into powder for later use; meanwhile, the metal substrate is degreased and polished for later use.

[0023] S2, preheating bisphenol A liquid epoxy resin at 45°C-75°C for 5-15 minutes, mixing it with two-dimensional flake phosphotungstic acid modified graphite phase carbon nitride and a curing agent, stirring for 60 minutes, and then ultrasonicating it for 5-15 minutes, and finally keeping it in a vacuum environment for 5-10 minutes to reduce bubbles in the whole system to obtain a coating.

[0024] The mixing mass ratio of the curing agent to the bisphenol A liquid epoxy resin is (0.7-0.9): 1, and preferably, the mixing mass ratio is 0.85: 1. The principle for selecting the amount of curing agent is to ensure the density and mechanical strength of the coating after the system is cured, and to control the curing time for easy construction.

[0025] Among them, bisphenol A type liquid epoxy resin and curing agent are taken, and a certain amount of phosphotungstic acid modified carbon nitride sample is taken at the same time.

[0026] S3, the coating of S3 was coated on the metal substrate using a film coater, and then the epoxy resin coating was stored at 100°C for 10 hours, the temperature was adjusted to 150°C and then stored for another 4 hours for curing, and the coating was successfully prepared.

[0027] In some embodiments of the present invention, in S1, the preparation process of g-C3N4 comprises the following steps: S101, Preparation of g-C3N4 by direct calcination of melamine in air Melamine (5 g) was placed in a crucible sealed with aluminum foil and heated in a muffle furnace at 5 °C min -1 The furnace was heated to 550 °C at a heating rate of 1000 ℃ and maintained for 4 h. After the furnace was cooled to room temperature naturally, the product g-C3N4 was collected.

[0028] Sintering of S102, g-C3N4 and phosphotungstic acid (HPW) 1.0 g of g-C3N4 was added to 15 mL of deionized water and ultrasonically dispersed for two hours to obtain a suspension. 5.0 g of HPW was added to the suspension while stirring. Stirring was continued for 4 hours (stirring for 1 hour and ultrasonication for 15 minutes, alternating four times); the suspension was slowly evaporated to dryness at a temperature of about 60°C and dried at a rate of 5°C·min -1 After heating at 110℃ for 12h, -1 The furnace was heated to 300°C at a heating rate of 200°C and sintered for 4 hours. After the furnace was cooled, the product was washed with deionized water for 3-4 times and dried at 60°C for 24 hours to obtain a sintered product of g-C3N4 and HPW. In the sintered product, g-C3N4 and HPW were composited with each other, and the -NH and -NH2 bonds at the edge of the g-C3N4 skeleton were combined with HPW.

[0029] In some embodiments of the present invention, the bisphenol A type liquid epoxy resin can be any one of E51 epoxy resin, EPON SU-8, Epon 828, NPEL-128 or DER 383.

[0030] In some embodiments of the present invention, the curing agent can be anhydride 80-150; amine at room temperature -80; polyamide 25-60.

[0031] In some specific embodiments, different resins and curing agents require different mixing ratios, and different curing times are required when preparing the coating.

[0032] In some specific embodiments of the present invention, in S2, the bisphenol A type liquid epoxy resin is selected from E51 epoxy resin, and the curing agent is selected from methylcyclohexene-1,2-dicarboxylic anhydride, and the mixing mass ratio of E51 epoxy resin to curing agent is 1.0:0.85. In S3, the E51 epoxy resin is preheated at 60° C. for minutes, and the raw materials of S2 are mixed together and stirred for 60 minutes, and then ultrasonicated for 5 minutes, and finally stored in a vacuum environment for 5-10 minutes.

[0033] The metal substrate in S1 can be a common metal or alloy material.

[0034] The second aspect of the present invention discloses a metal anti-corrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin obtained by the above-mentioned preparation method, wherein the main material of the coating is epoxy resin, and flaky phosphotungstic acid modified carbon nitride is added to the epoxy resin, wherein the phosphotungstic acid modified carbon nitride accounts for 0.25 wt%~0.75 wt% of the entire coating.

[0035] The following is further described in conjunction with specific embodiments: Comparative Example 1 Step 1, taking E51 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as base materials, the ratio of E51 epoxy resin to curing agent is 1.0:0.85.

[0036] Step 2, preheating E51 epoxy resin at 60°C for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally keeping in a vacuum environment for 5 minutes to obtain a mixture.

[0037] Step 3, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then storing the epoxy resin coating at 100°C for 10 hours, adjusting the temperature to 150°C and storing it for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0038] Example 1 Step 1, after modifying graphite phase carbon nitride with phosphotungstic acid, grind it into powder for later use; at the same time, degrease and polish the Q235 substrate for later use; Step 2, take E51 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as base materials, the ratio of E51 epoxy resin to curing agent is 1.0:0.85, and at the same time take 0.25 wt% of the mass of E51 epoxy resin phosphotungstic acid modified carbon nitride sample.

[0039] Step 3, preheating E51 epoxy resin at 60° C. for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally keeping in a vacuum environment for 5 minutes to obtain a mixture.

[0040] Step 4, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then the epoxy resin coating is stored at 100°C for 10 hours, the temperature is adjusted to 150°C, and then stored for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0041] For the phosphotungstic acid modified carbon nitride filler prepared in step 1 in Example 1, the corresponding test was performed to prove the accuracy of the filler synthesis. The filler infrared test results are as follows: Figure 1 As shown in the figure, according to the infrared test results, compared with the infrared spectrum of carbon nitride, the phosphotungstic acid modified carbon nitride has a wavelength of 4000~3500 cm -1 There is a strong and broad-spectrum -OH vibration absorption peak at 1450~1300 cm -1 In the range of 1200~1000 cm -1 In the range of 850-750 cm -1 Within the range, the WOW bridge bond in the phosphotungstic acid molecule absorbs significantly, which is a characteristic of the molecular structure of phosphotungstic acid, proving that the synthesis of phosphotungstic acid modified carbon nitride material is successful.

[0042] Example 2 Step 1, after modifying graphite phase carbon nitride with phosphotungstic acid, grind it into powder for later use; at the same time, degrease and polish the Q235 substrate for later use; Step 2, taking E51 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as base materials, the ratio of E51 epoxy resin to curing agent is 1.0:0.85, and taking 0.5 wt% of the mass of E51 epoxy resin of phosphotungstic acid modified carbon nitride sample.

[0043] Step 3, preheating E51 epoxy resin at 60° C. for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally keeping in a vacuum environment for 5 minutes to obtain a mixture.

[0044] Step 4, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then the epoxy resin coating is stored at 100°C for 10 hours, the temperature is adjusted to 150°C, and then stored for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0045] Example 3 Step 1, after modifying graphite phase carbon nitride with phosphotungstic acid, grind it into powder for later use; at the same time, degrease and polish the Q235 substrate for later use; Step 2, taking E51 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as base materials, the ratio of E51 epoxy resin to curing agent is 1.0:0.85, and taking 0.75 wt% of the mass of E51 epoxy resin of phosphotungstic acid modified carbon nitride sample.

[0046] Step 3, preheating E51 epoxy resin at 60° C. for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally keeping in a vacuum environment for 5 minutes to obtain a mixture.

[0047] Step 4, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then the epoxy resin coating is stored at 100°C for 10 hours, the temperature is adjusted to 150°C, and then stored for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0048] In this embodiment, the mass of the added phosphotungstic acid modified carbon nitride sample accounts for 0.75wt% of the mass of the E51 epoxy resin.

[0049] The samples of the comparative example, embodiment 1, embodiment 2, and embodiment 3 were analyzed and tested, and the test results were compared to analyze the anti-corrosion performance of different samples. A continuous salt spray test was conducted using a salt spray test chamber to detect the corrosion resistance of the coating in a salt spray environment and analyze the durability and reliability of the coating. The test results are as follows: Figure 2 As shown, according to the test results analysis in the salt spray test results, compared with the pure epoxy resin coating and the epoxy resin coating with phosphotungstic acid modified carbon nitride filler, the pure epoxy resin coating rusts earlier and is obviously corroded, that is, the corrosion protection durability is poor and it is easy to be corroded and cracked. The epoxy resin coating with phosphotungstic acid modified carbon nitride filler shows the best protection effect at 0.5 wt%.

[0050] The hydrophilicity of the coating is very important for the anti-corrosion performance of the coating, so the coating is tested for water contact angle. The test results are as follows: Figure 3 As shown in Table 1, according to the test results, the addition of a certain amount of phosphotungstic acid modified carbon nitride filler can effectively reduce the hydrophilicity of the coating, which is an improvement in the corrosion protection of the coating, but excessive filler will increase the hydrophilicity of the coating and cause the hydrophilicity to drop significantly. In the test results, 0.5 wt% addition is still the best performance.

[0051] Table 1 Water contact angle test results

[0052] The cross section of the novel epoxy resin coating prepared by the present invention was observed by scanning electron microscopy, and the performance improvement of the epoxy resin coating was analyzed from a microscopic perspective. The surface test results are as follows: Figure 4As shown in the figure, with the increase of phosphotungstic acid modified carbon nitride filler, filler particles appear on the surface of the epoxy resin coating in the scanning electron microscope view, which illustrates the uniformity of the filler dispersion in the epoxy resin. At the same time, when the addition amount reaches 0.75 wt%, the filler agglomerates and larger agglomerated particles appear on the coating surface, which can also explain why the 0.75 wt% coating performs poorly in the salt spray test.

[0053] Example 4 Step 1, after modifying graphite phase carbon nitride with phosphotungstic acid, grind it into powder for later use; at the same time, degrease and polish the Q235 substrate for later use; Step 2, take EPON SU-8 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as the base material, the ratio of E51 epoxy resin to curing agent is 1.0:0.8, and at the same time, 0.25 wt% of the mass of EPON SU-8 epoxy resin is used as the phosphotungstic acid modified carbon nitride sample.

[0054] Step 3, preheating EPON SU-8 epoxy resin at 60° C. for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally keeping in a vacuum environment for 5 minutes to obtain a mixture.

[0055] Step 4, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then the epoxy resin coating is stored at 100°C for 10 hours, the temperature is adjusted to 150°C, and then stored for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0056] Example 5 Step 1, after modifying graphite phase carbon nitride with phosphotungstic acid, grind it into powder for later use; at the same time, degrease and polish the Q235 substrate for later use; Step 2, take Epon828 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as the base material, the ratio of E51 epoxy resin to curing agent is 1:0.7, and at the same time, 0.25 wt% of the mass of EPON SU-8 epoxy resin is used as the phosphotungstic acid modified carbon nitride sample.

[0057] Step 3, preheating EPON SU-8 epoxy resin at 60° C. for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally storing in a vacuum environment for 10 minutes to obtain a mixture.

[0058] Step 4, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then the epoxy resin coating is stored at 100°C for 10 hours, the temperature is adjusted to 150°C, and then stored for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0059] Example 6 Step 1, after modifying graphite phase carbon nitride with phosphotungstic acid, grind it into powder for later use; at the same time, degrease and polish the Q235 substrate for later use; Step 2, take EPON SU-8 epoxy resin and curing agent methylcyclohexene-1,2-dicarboxylic anhydride as the base material, the ratio of E51 epoxy resin to curing agent is 1:0.9, and at the same time, 0.25 wt% of the mass of EPON SU-8 epoxy resin is used as the phosphotungstic acid modified carbon nitride sample.

[0060] Step 3, preheating NPEL-128 epoxy resin at 60° C. for 10 minutes, mixing the raw materials in step 2 together, stirring for 60 minutes, ultrasonicating for 5 minutes, and finally storing in a vacuum environment for 8 minutes to obtain a mixture.

[0061] Step 4, using a coating applicator to coat the mixture of step 3 on the Q235 substrate, and then the epoxy resin coating is stored at 100°C for 10 hours, the temperature is adjusted to 150°C, and then stored for another 4 hours for natural cooling and curing, and the coating is successfully prepared.

[0062] Example 7 In this embodiment, the bisphenol A liquid epoxy resin is preheated at 45° C. for 15 minutes before being mixed with the curing agent and the phosphotungstic acid modified carbon nitride. The remaining parts not involved are the same as those in Example 1.

[0063] Example 8 In this embodiment, the bisphenol A liquid epoxy resin is preheated at 75° C. for 5 minutes before being mixed with the curing agent and the phosphotungstic acid modified carbon nitride. The remaining parts not involved are the same as those in Example 1.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin, characterized in that: The following steps are involved: S1, modifying graphite phase carbon nitride by phosphotungstic acid to obtain two-dimensional sheet-like phosphotungstic acid-modified carbon nitride; S2, mixing bisphenol A liquid epoxy resin, a curing agent and phosphotungstic acid modified carbon nitride and stirring them uniformly, and obtaining a coating after ultrasonic treatment; S3, coating the paint on the metal substrate, and obtaining the epoxy resin metal anti-corrosion coating after drying and curing.

2. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: In S2, the mixing mass ratio of bisphenol A liquid epoxy resin and curing agent is 1:(0.7-0.9).

3. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: The mass fraction of phosphotungstic acid modified carbon nitride in the coating is 0.25 wt%~0.75 wt%.

4. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: In S2, the bisphenol A liquid epoxy resin is preheated at 45°C-75°C for 5-15 minutes before being mixed with the curing agent and the phosphotungstic acid modified carbon nitride.

5. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: In S2, the ultrasonic treatment time is 5-15 minutes.

6. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: In S2, the coating was kept in a vacuum environment for 5-10 minutes after ultrasonic treatment.

7. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: In S2, the curing agent is any one of anhydride 80-150, amine room temperature -80 or polyamide 25-60.

8. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to claim 1, characterized in that: The specific process of S3 is: the coating is applied on the metal substrate, first stored at 100°C for 10 hours, and then stored at 150°C for another 4 hours.

9. The method for preparing a metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin according to any one of claims 1 to 8, characterized in that: In S1, the process of treating graphite phase carbon nitride with phosphotungstic acid is as follows: calcining melamine to prepare g-C3N4, and sintering g-C3N4 and phosphotungstic acid to obtain phosphotungstic acid modified carbon nitride.

10. A metal anticorrosion coating based on phosphotungstic acid modified carbon nitride / epoxy resin prepared by any one of the preparation methods of claims 1 to 9, characterized in that: The invention comprises an epoxy resin in which two-dimensional sheet-like phosphotungstic acid-modified carbon nitride is embedded.